Correlation Analysis of Genotypes and Phenotypes in Chinese Male Pediatric Patients With Congenital Hypogonadotropic Hypogonadism - Wang, Yi; Qin, Miao; Fan, Lijun; Gong, Chunxiu (Frontiers in Endocrinology, 2022)
Congenital hypogonadotropic hypogonadism (CHH) can be divided into Kallmann syndrome (KS) and normosmic HH (nHH). The clinical and genetic characteristics of CHH have been studied in adults, but less in pre-adults. The medical records of patients with CHH in our gonad disease database from 2008 to 2020 were evaluated. In total, 125 patients aged 0 to 18 years were enrolled in our study. KS patients had a higher incidence of micropenis compared with nHH (86.2% vs. 65.8%, p=0.009), and 7 patients (5.6%) had hypospadias. Among the 39 patients with traceable family history, delayed puberty, KS/nHH, and olfactory abnormalities accounted for 56.4%, 17.9%, and 15.4%, respectively. In total, 65 patients completed the hCG prolongation test after undergoing the standard hCG test, and the testosterone levels of 24 patients (22.9%) were still lower than 100 ng/dL. In 77 patients, 25 CHH-related genes were identified, including digenic and trigenic mutations in 23 and 3 patients, respectively. The proportion of oligogenic mutations was significantly higher than that in our previous study (27.7% vs. 9.8%). The most common pathogenic genes were FGFR1, PROKR2, CHD7 and ANOS1. The incidence rate of the genes named above was 21.3%, 18.1%, 12.8% and 11.7%, respectively; all were higher than those in adults (<10%). Most mutations in CHH probands were private, except for W178S in PROKR2, V560I in ANOS1, H63D in HS6ST1, and P191L and S671L in IL17RD. By analyzing family history and genes, we found that both PROKR2 and KISS1R may also be shared between constitutional delay of growth and puberty (CDGP) and CHH. L173R of PROKR2 accounts for 40% of the CHH population in Europe and the United States; W178S of PROKRR2 accounts for 58.8% of Chinese CHH patients. Micropenis and cryptorchidism are important cues for CHH in children. They are more common in pediatric patients than in adult patients. It is not rare of Leydig cell dysfunction (dual CHH), neither of oligogenic mutations diagnosed CHH in children. Both PROKR2 and KISS1R maybe the potential shared pathogenic genes of CDGP and CHH, and W178S in PROKRR2 may be a founder mutation in Chinese CHH patients.